A educação popular nos inquéritos policiais militares pós-1964 - Afonso Celso Scocuglia (EccoS – Revista Científica)
This work is part of a reconstruction of histories and memories from the dictatorship and the political education after-1964. In it, specifically, the controllers of the Campaign of Popular Education (CEPLAR) of the Paraíba State are involved. Its principal source was Military Police Inquest (IPM) restored by the Army, that accused 52 people and moved in Superior Military Court (STM) (1964-1969) and, thus, it is also included the performance of the delators and responsible for the action at law. In terms of methodology, in this study it is linked bibliographical research to documentary research and, beyond the verbal sources (and writings) supplied by the defendants by IPM, and it is used the speech analysis as a tool and a procedure. About the theoretical recital, it was searched foundations as past/present inseparability (LE GOFF, 1992; BLOCH, 1987), history of the present time (RÉMOND, 1996), monitoring and punishment (FOUCAULT, 1979; 1986), hegemony and intellectuals role (GRAMSCI, 1982), ideology and States devices (ALTHUSSER, 1980). Furthermore, we added studies on military justice (LEMOS, 2004), the friendly guardianship of the military on the Brazilian civilians (ZAVERUCHA, 1996), the assembly of the State of class (DREIFUSS, 1981), the manifest dictatorship (GASPARI, 2004) and the military State (GERMANO, 1993).